Stability with probability I for solutions of linear stochastic differential-difference Ito’s equations - Zelentsovsky , A. L. (Ukrains’kyi Matematychnyi Zhurnal, 2025)
Conditions for absolute (independent of lags) asymptotic stability with probability 1 of systems of stochastic equations cited in the title of this paper are obtained. The proposed approach allows us to reduce the problem of analyzing stability to determination of the conditions for the existence of a positively determined solution of a linear matrix equation. These conditions are stated in terms of locations of eigenvalues of the matrix constructed from the elements of the matrices of the initial system.